Mitochondrial Group II Introns, Cytochrome c Oxidase, and Senescence in Podospora anserina - Begel, Odile (American Society for Microbiology, 1999)
Podospora anserina is a filamentous fungus with a limited life span. It expresses a degenerative syndrome called senescence, which is always associated with the accumulation of circular molecules (senDNAs) containing specific regions of the mitochondrial chromosome. A mobile group II intron (α) has been thought to play a prominent role in this syndrome. Intron α is the first intron of the cytochrome c oxidase subunit I gene (COX1). Mitochondrial mutants that escape the senescence process are missing this intron, as well as the first exon of the COX1 gene. We describe here the first mutant of P. anserina that has the α sequence precisely deleted and whose cytochrome c oxidase activity is identical to that of wild-type cells. The integration site of the intron is slightly modified, and this change prevents efficient homing of intron α. We show here that this mutant displays a senescence syndrome similar to that of the wild type and that its life span is increased about twofold. The introduction of a related group II intron into the mitochondrial genome of the mutant does not restore the wild-type life span. These data clearly demonstrate that intron α is not the specific senescence factor but rather an accelerator or amplifier of the senescence process. They emphasize the role that intron α plays in the instability of the mitochondrial chromosome and the link between this instability and longevity. Our results strongly support the idea that in Podospora, “immortality” can be acquired not by the absence of intron α but rather by the lack of active cytochrome c oxidase.